2005
DOI: 10.1007/bf02985570
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Takotsubo cardiomyopathy (transient left ventricular apical ballooning) using99mTc-tetrofosmin,123I-BMIPP,123I-MIBG and99mTc-PYP myocardial SPECT

Abstract: Takotsubo cardiomyopathy might represent a stunned myocardium caused by a disturbance of the coronary microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A follow-up observation study using 201 Tl, 123 IBMIPP, 123 I-MIBG SPECT showed that the recovery of the decreased uptake mostly occurred in the order of 201Tl, 123I-BMIPP, and 123I-MIBG. [23][24][25] Moreover, Suzuki et al have measured regional cerebral blood flow, a well-established index of brain activity using 99m Tc ethyl cysteinate dimmer SPECT, and demonstrated a significant cerebral blood flow increase in the hippocampus, brainstem, and basal ganglia paralleled by a decrease in the prefrontal cortex in the acute phase of TTC. 26 Although these changes gradually subsided, they were still present in the chronic phase of TTC even after the cardiac wall motion abnormalities had disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up observation study using 201 Tl, 123 IBMIPP, 123 I-MIBG SPECT showed that the recovery of the decreased uptake mostly occurred in the order of 201Tl, 123I-BMIPP, and 123I-MIBG. [23][24][25] Moreover, Suzuki et al have measured regional cerebral blood flow, a well-established index of brain activity using 99m Tc ethyl cysteinate dimmer SPECT, and demonstrated a significant cerebral blood flow increase in the hippocampus, brainstem, and basal ganglia paralleled by a decrease in the prefrontal cortex in the acute phase of TTC. 26 Although these changes gradually subsided, they were still present in the chronic phase of TTC even after the cardiac wall motion abnormalities had disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial perfusion imaging during the acute phase typically demonstrates normal or mildly reduced uptake in the dysfunctional segments. Normalisation of uptake occurs in association with wall motion recovery 79,80 …”
Section: Diagnosismentioning
confidence: 99%
“…However, cases of TS with delayed gadolinium uptake have been reported [133], giving rise to doubts of ischemia. Myocardial SPECT reveals a fall in technetium-99m tetrofosmin uptake in the acute phase, indicative of a decrease in myocardial perfusion [100,135,136]. Reversible alterations of a number of radioactive tracers, such as 123 I-BMIPP and 123 I-MIBG, could indicate a reduction in fatty acid and glucose metabolism, alterations of coronary microcirculation, or a possible imbalance in the sympathetic innervation between the apical and basal regions [137].…”
Section: Imaging Studiesmentioning
confidence: 99%